Исследование температурного режима работы зарядного блока электроразрядных погружных устройств - Хвощан, Олег Вильямович (НТУ "ХПИ", 2016)
С использованием программных продуктов MathCAD и Femlab проведен теоретический расчет температурного поля зарядного блока высоковольтных электроразрядных погружных устройств с выходной мощностью 1 кВА и промежуточным преобразованием энергии на частоте 15 кГц. Определены критические к перегреву элементы конструкции зарядного блока, включающего инвертор напряжения, высоковольтный трансформатор и высоковольтный выпрямитель. Проведено сравнение результатов теоретических расчетов с экспериментальными данными. Предложены варианты решений для снижения температур перегрева элементов.

The article deals with improving the functioning of electrohydropulse devices for the treatment of oil, water intake (artesian), injection wells, which are widely used at the present time in Europe (Ukraine, Russia, France, Slovenia), Asia (China, Kazakhstan, Uzbekistan), North America (USA, Canada). Using software products MathCAD and Femlab a theoretical calculation of the temperature field of the charging unit of electrodischarge submersible devices with useful capacity of 1 kW and the intermediate energy conversion at a frequency of 15 kHz is carried out. The critical-overheating elements of the charging unit structure comprising a voltage inverter, a high voltage transformer and highvoltage rectifier are identified. A comparison of the results of theoretical calculation with experimental data received in the laboratories of the Department of Pulse Treatment of Disperse Systems of the Institute of Pulse Processes and Technologies of the National Academy of Sciences of Ukraine is carried out. The variants of solutions to reduce the temperature of overheating components are offered.
The research of the temperature mode of the charging unit of electric submersible devices
Keywords: температура перегрева; теплопроводность; диэлектрик; КПД; призабойная зона пласта; overheating temperature; thermal conductivity; dielectric